Influencia de la actividad física en el rendimiento académico de los estudiantes entre 15-16 años en la Unidad Educativa Francisco Huerta Rendón - Arteaga Gilces, Jandry Manuel (2025)
This research aims to analyze the influence of physical activity on the academic performance of 15- to 16-year-old students at the Francisco Huerta Rendón Educational Unit in Babahoyo, Ecuador. A correlational design was used to assess the relationship between the perceived level of physical activity and academic performance. The sample consisted of 63 third-year high school students, selected in an intentional non-probabilistic manner, also including teachers and administrators. Statistical techniques were used to evaluate the data, such as frequency tables, descriptive statistics (mean, median, mode), and chi-square analysis to explore the relationships between variables. The results indicate a significant association between physical activity and academic performance, with a p-value < 0.06, indicating that participation in physical activities is associated with better academic performance. It also revealed that students who regularly participate in physical activities tend to show better academic performance compared to those who participate occasionally or not. The findings reinforce the need for educational policies that promote the integration of physical activity into the school curriculum and address existing barriers to its effective implementation.